Peran Income Audit Guna Meningkatkan Akurasi Pencatatan dan Pelaporan Pendapatan di Vasa Hotel Surabaya - Mario Ferdinandus Tele; Condro Widodo (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The role of revenue audit in improving the accuracy of revenue recording and reporting is critical to ensuring the integrity of financial information at Vasa Hotel Surabaya. Through a systematic analysis of the hotel's revenue audit activities, this study explores how comprehensive training for the audit team, implementation of strong internal controls, and efficient revenue verification significantly contribute to the accuracy of financial data. This approach not only supports a more informed and data-driven management decision-making process, but also facilitates transparency and accountability in hotel operations. The implementation of the strategy showed an improvement in accurate financial reporting, which was the result of cross-verification, regular audits, and evaluation of revenue-related processes, resulting in more reliable financial statements and improved hotel operational performance. This research underscores the importance of effective revenue auditing as a vital tool to sharpen financial integrity and business sustainability in the hospitality industry.